Karakterisasi Senyawa Metabolit Sekunder Daun Kayu Putih (Melaleuca Leucadendra) Dan Potensi Bioaktivitasnya Dalam Bidang Farmasi - Ni’matullathifah; Ardi Mustakim (MUARA KESEHATAN : Jurnal Ilmiah Ilmu Kesehatan, 2026)
Eucalyptus (Melaleuca leucadendra) is a medicinal plant found abundantly in tropical Indonesia and is widely known as a source of essential oils with diverse pharmacological activities. Eucalyptus leaves contain various secondary metabolites, such as monoterpenes (especially 1,8-cineole), flavonoids, tannins, saponins, and phenolic compounds, which play a role in antibacterial, anti-inflammatory, antioxidant, and analgesic activities. This study aims to examine the characteristics of secondary metabolites in eucalyptus leaves and evaluate their potential bioactivity in the pharmaceutical field. The method used was a systematic literature review (SLR) of scientific publications from 2018–2025 that discussed the phytochemistry and pharmacological activities of Melaleuca leucadendra. The results indicate that the main constituent of eucalyptus leaf essential oil, particularly 1,8-cineole, has antimicrobial activity against Gram-positive and Gram-negative bacteria and acts as an anti-inflammatory agent by inhibiting inflammatory mediators. Furthermore, the flavonoid and phenolic compounds contribute to antioxidant activity, which is important in protecting cells from oxidative stress. These findings confirm that eucalyptus leaves have significant potential for development as a raw material for pharmaceutical preparations, both topical and inhaled